Making GHG emissions trading work – Crucial issues in designing national and international emmissions trading systems - Sonja Butzengeiger; Regina Betz; Sven Bode (Hamburg Institute of International Economics (HWWA), 2001)
Art. 17 of the Kyoto Protocol defines International Emissions Trading exclusively on country level, sub-national entities like industrial installations or households are not included initially. However, there are some arguments for such an expansion, of which the most important ones are a significant increase of the overall efficiency of the trading system as well as an increase of market liquidity. In the first part of this paper, the options for an inclusion of sub-national entities are analysed, concluding that AAUs should not be allocated to participants directly. Instead, there are several options how those entities can be included in International Emissions Trading as defined in the Kyoto-Protocol in an indirect way. The second part of the paper elaborates on the design options of national trading systems. All governments planning to introduce a domestic emissions trading scheme covering entities need to consider several design parameters, e.g. the characteristics of emission targets, participants of the trading scheme, participation mode, covered gases, non-compliance provisions, etc. We analyse and evaluate the options for each of those aspects, having in mind that the design of a trading system must assure its environmental integrity and keep transaction costs low at the same time. – – Der ?Internationale Emissionshandel (IET)? wird nach Artikel 17 des Kyoto-Protokolls zunächst ausschließlich auf Staatenebene definiert. Es sprechen jedoch einige Gründe dafür, den Emissionshandel auch auf nicht staatliche Einheiten, wie z.B. industrielle und/oder private Emittenten auszudehnen. Die wesentlichen Vorteile sind die zu erwartende deutliche Erhöhung der Effizienz des Handelssystems sowie der Marktliquidität. Wir analysieren die verschiedenen Möglichkeiten einer derartigen Ausweitung des Emissionshandels. Eine direkte Einbeziehung subnationaler Einheiten durch die Zuteilung von Emissionsrechten nach dem Kyoto-Protokoll (AAUs) in den IET erscheint nicht empfehlenswert. Statt dessen bestehen verschiedene Möglichkeiten der indirekten Einbeziehung, bei der nationale ?Währungen? für Emissionsrechte ausgegeben werden. Zudem werden die verschiedenen Ausgestaltungsparameter analysiert, die bei der Einrichtung eines (inter-)nationalen Emissionshandelssystems berücksichtigt werden müssen. Dies sind u.a. die Definition von Teilnehmerkreis, Teilnahmemodus, Art der Emissionsziele, Einbeziehung von Gasen, Einbeziehung der projektbasierten Mechanismen sowie Strafregelungen. Die einzelnen Ausgestaltungsoptionen werden evaluiert, insbesondere hinsichtlich der grundlegenden Ziele des Emissionshandels: Sicherung der ökologischen Integrität bei Minimierung der entstehenden Kosten.
Keywords: 330; Klimaschutz; Kohlendioxid; Luftverunreinigung; Umweltzertifikat; Internationale Umweltpolitik; Dezentralisierung; Welt